Antibacterial ceramic and its preparation process
By using specific proportion of kaolin, aluminum alum soil and other materials and resin in ceramic materials, combined with bacteriostatic agents, the color of the existing antibacterial ceramics is easy to receive light, high cost and low compressive strength, and realize high -efficiency antibacterials Increases of sterilization and pressure resistance.
Patent Information
- Application Number
- CN202410847874.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The existing antibacterial ceramics have problems such as the color of silver-based antibacterial agents being easily affected by light, high cost, and low compressive strength of ceramic materials.
The use of kaolin, aluminum soil, long stone, talc, quartz, decentralizers, bacteriostatic agents and resin and other materials, through specific proportion and firing process, forming ceramic materials with excellent antibacterial and sterilization effects Pressure strength.
The efficient antibacterial and sterilization effect of ceramic materials has been achieved, and its compressive strength is improved, the cost is reduced and the scope of applicability is reduced.
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic technology, and in particular to an antibacterial ceramic and a preparation process thereof. Background Art
[0002] Antibacterial ceramics refer to ceramic products with antibacterial functions. Inorganic antibacterial agents are added to a certain stage of ceramic preparation to make the ceramics have antibacterial effects. It is a product that combines antibacterial technology with ceramic materials, and is also a product of the combination of material science and microbiology. Using antibacterial daily-use porcelain as tableware, tea sets, etc. can greatly reduce the bacteria introduced from food and drinking water.
[0003] In the related art, antibacterial ceramics are mainly silver-loaded antibacterial ceramics, which have the characteristics of low toxicity and good antibacterial performance. However, there are also some problems. For example, the color of silver-based antibacterial ceramics is affected to a certain extent by the influence of external light sources, and the silver raw material is precious and scarce, resulting in high costs. At the same time, although the ceramic material in the related art has high hardness, its compressive strength is low.
[0004] Application Contents
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide an antibacterial ceramic material having good antibacterial properties.
[0006] Specifically, the first aspect of the present application provides an antibacterial ceramic, including the following preparation raw materials:
[0007] Kaolin, bauxite, feldspar, talc, quartz, dispersants, antimicrobial agents and resins;
[0008] The resin comprises the following preparation raw materials:
[0009] 3-Fluorophenol, 4-hydroxyphenylboronic acid, formaldehyde, melamine, boric acid, phenyltriethoxysilane, and a base.
[0010] According to one of the technical solutions of this application, at least the following beneficial effects are achieved:
[0011] Kaolin: Mainly provides SiO2 and Al2O3 for glaze, has good binding properties and is used to adjust stability.
[0012] Bauxite: Bauxite is rich in substances such as aluminum oxide, which have high hardness and wear resistance. Therefore, bauxite can increase the hardness and wear resistance of ceramic materials, thereby improving their durability and reliability.
[0013] Feldspar: mainly introduces alkali metal elements; feldspar can promote the firing of glass phase and increase the degree of vitrification, which is beneficial to reduce the water absorption rate of ceramics, reduce the firing temperature, promote the sintering reaction, improve the strength, and widen the sintering temperature range. When preparing the raw materials for melting, feldspar melts to form glass and melts part of quartz at high temperature, promoting the melting reaction, and no longer crystallizes after cooling. After cooling, it exists in a transparent glass state, increasing the transparency and glossiness of the ceramic material.
[0014] Talc: Mainly provides MgO for ceramic materials. Talc has a strong fluxing effect on raw materials and can reduce the sintering temperature of the green body. At high temperatures, it generates a glass phase containing MgO, which has a large surface tension and low viscosity, which is beneficial to reducing shrinkage and improving gloss. Talc can increase the opacity and whiteness of the glaze.
[0015] Quartz: It mainly forms the silicon-oxygen skeleton of ceramics during the melting process at high temperature and is the main component of ceramic materials. Quartz can improve the wear resistance and chemical stability of ceramic materials.
[0016] Dispersant: Improve and enhance the dispersibility of ceramic powder in liquid medium, thereby improving the fluidity and stability of ceramic slurry.
[0017] Under the action of alkali, formaldehyde molecules preferentially attack hydrogen on some carbon atoms of phenolic hydroxyl groups (3-fluorophenol, 4-hydroxyphenylboronic acid) to form methylol groups, and obtain monosubstituted methylolphenol, disubstituted methylolphenol and trisubstituted methylolphenol. The obtained methylolphenol undergoes a dehydration reaction with hydrogen on melamine amino groups to form -CN bonds, or undergoes a dehydration reaction with triazine ring oligomers generated by methylene cross-linking reaction of melamine and formaldehyde; the boron element in boric acid is introduced into the resin structure through the esterification reaction of B-OH and phenolic hydroxyl groups, and finally forms a copolymer with a cross-linked structure. The present invention utilizes the resin in the mixed slurry as a carbon source, fluorine element, silicon element, boron element and nitrogen element, and produces silicon nitride, silicon carbide and boron nitride during the sintering process, which play a toughening role on the ceramic material, thereby increasing the compressive strength of the ceramic; at the same time, the phenolic resin can also play a certain stabilizing role on the slurry during the formation of the slurry, so as to be evenly dispersed in the inorganic material, thereby further improving the compressive strength of the ceramic material.
[0018] Boron element acts as an antibacterial factor, which enables the ceramic to release antibacterial factors as a whole, and has obvious antibacterial and bactericidal effects.
[0019] The present application forms the raw material for making ceramics through reasonable proportioning of the components, and the finished ceramics have excellent antibacterial and bactericidal effects; at the same time, a ceramic material with high compressive strength is also produced.
[0020] According to some embodiments of the present application, the antibacterial ceramic comprises the following raw materials in parts by weight:
[0021] 100 parts of kaolin, 50 to 100 parts of bauxite, 50 to 100 parts of feldspar, 5 to 10 parts of talc, 50 to 100 parts of quartz, 5 to 10 parts of dispersant, 0.1 to 0.2 parts of antibacterial agent and 10 to 30 parts of resin.
[0022] According to some embodiments of the present application, the resin includes the following preparation raw materials in parts by weight:
[0023] 100 parts of 3-fluorophenol, 400 to 500 parts of 4-hydroxyphenylboric acid, 100 to 200 parts of formaldehyde, 100 to 200 parts of melamine, 50 to 100 parts of boric acid, 300 to 400 parts of phenyltriethoxysilane and 1 to 10 parts of alkali.
[0024] According to some embodiments of the present application, the dispersant includes at least one of polyethylene glycol and sodium polyacrylate.
[0025] According to some embodiments of the present application, the feldspar includes at least one of albite and potassium feldspar.
[0026] According to some embodiments of the present application, the mass ratio of albite to potassium feldspar is 1:0.5-2.
[0027] According to some embodiments of the present application, the raw materials for preparing the antibacterial ceramic further include water.
[0028] According to some embodiments of the present application, the mass ratio of kaolin to water is 1:0.5-1.5.
[0029] According to some embodiments of the present application, the antibacterial agent is at least one of zinc oxide and silver ion antibacterial agents.
[0030] The antibacterial agent is formed by specifically selecting zinc oxide and silver ion antibacterial agents to form a compound antibacterial agent, so that the antibacterial effect is better.
[0031] According to some embodiments of the present application, the mass ratio of the zinc oxide to the silver ion antibacterial agent is 1:1.9-2.1.
[0032] By specifically selecting the mass ratio of zinc oxide and silver ion antibacterial agents, the antibacterial effect of the ceramic material is further improved, thereby better broadening the scope of application of the ceramic material.
[0033] According to some embodiments of the present application, the base includes at least one of sodium hydroxide and ammonia monohydrate.
[0034] According to some embodiments of the present application, the flexural strength of the antibacterial ceramic is 150 MPa to 200 MPa.
[0035] According to some embodiments of the present application, the antibacterial rate of the antibacterial ceramic is 95% to 99.9%.
[0036] The second aspect of the present application discloses a preparation process of the above antibacterial ceramic, comprising the following steps:
[0037] Mixing kaolin, bauxite, feldspar, talc, quartz, dispersant, antibacterial agent, resin and water to prepare slurry, and shaping the slurry to prepare a green body;
[0038] Firing the green body;
[0039] The firing temperature is 400°C to 1300°C.
[0040] According to some embodiments of the present application, the firing includes a first heat preservation and a second heat preservation.
[0041] According to some embodiments of the present application, the temperature of the first insulation is 400°C to 600°C.
[0042] According to some embodiments of the present application, the first insulation time is 2h to 4h.
[0043] During the first heat preservation process, dehalogenation assisted carbonization. The F atom on the benzene ring of 3-fluorophenol formed a hydrogen bond with the adjacent H atom in the resin structure. Therefore, even at a relatively low carbonization temperature, HF was removed between the -CF bond on the benzene ring and an adjacent -NH bond to directly form a heterocycle, thereby forming a sp 2 conjugated carbon plane; thereby promoting the formation of carbon materials, while further promoting the subsequent formation of silicon carbide materials.
[0044] According to some embodiments of the present application, the temperature of the second insulation is 1200°C to 1300°C.
[0045] According to some embodiments of the present application, the second insulation time is 10 hours to 14 hours.
[0046] According to some embodiments of the present application, the firing includes a first heating, a first heat preservation, a second heating and a second heat preservation.
[0047] According to some embodiments of the present application, the first heating rate is 10°C / min to 20°C / min.
[0048] According to some embodiments of the present application, the second heating rate is 10°C / min to 20°C / min.
[0049] According to some embodiments of the present application, the method for preparing the resin comprises the following steps:
[0050] S1, mixing boric acid and phenyltriethoxysilane to react to obtain a first mixture;
[0051] S2, mixing the first mixture, 3-fluorophenol, 4-hydroxyphenylboric acid, formaldehyde, melamine, alkali and water and then hydroheating.
[0052] According to some embodiments of the present application, the reaction temperature in step S1 is 60°C to 80°C.
[0053] According to some embodiments of the present application, the reaction time of step S1 is 10 h to 20 h.
[0054] According to some embodiments of the present application, the hydrothermal temperature in step S2 is 150° C. to 170° C.;
[0055] According to some embodiments of the present application, the hydrothermal time in step S2 is 3 h to 5 h. DETAILED DESCRIPTION
[0056] The following description will be described in detail as appropriate for the embodiments specifically disclosed in the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually identical structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0057] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0060] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0061] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0062] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] Kaolin: Kaolin, mesh number is 1250 mesh.
[0064] Bauxite: Bauxite, mesh number is 325 mesh.
[0065] Feldspar: Albite (325 mesh), Potassium feldspar (325 mesh).
[0066] Talc: Talc powder, mesh size is 325 mesh.
[0067] Quartz: Quartz sand, mesh number is 600 mesh.
[0068] Dispersant: polyethylene glycol PEG-8000; sodium polyacrylate, Anhui Water Guard Environmental Protection Technology Co., Ltd., SWS-A02.
[0069] Zinc oxide was purchased from Shandong Wangtong Chemical Co., Ltd., CAS number: 1314-13-2.
[0070] Silver ion antibacterial agent was purchased from Nanjing Tianshi Landun Biotechnology Co., Ltd., model: LD940, inorganic nanosilver antibacterial agent.
[0071] Example 1
[0072] This embodiment is an antibacterial ceramic, which is composed of the following raw materials in parts by weight:
[0073] 100 parts of kaolin, 60 parts of bauxite, 50 parts of feldspar, 6 parts of talc, 70 parts of quartz, 10 parts of dispersant, 0.1 parts of antibacterial agent, 30 parts of resin and 100 parts of water.
[0074] The dispersant is composed of polyethylene glycol and sodium polyacrylate in a mass ratio of 1:1.
[0075] Feldspar is composed of albite and potassium feldspar, and the mass ratio of albite to potassium feldspar is 1:1.
[0076] The antibacterial agent is a compound of zinc oxide and silver ion antibacterial agent, and the mass ratio of zinc oxide to silver ion antibacterial agent is 1:2.
[0077] The resin includes the following raw materials in parts by weight:
[0078] 100 parts of 3-fluorophenol, 490 parts of 4-hydroxyphenylboric acid, 160 parts of formaldehyde, 120 parts of melamine, 60 parts of boric acid, 340 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0079] The preparation method of the resin consists of the following steps:
[0080] S1, mixing boric acid and phenyltriethoxysilane for reaction (reacting at 60° C. for 12 hours) to obtain a first mixture;
[0081] S2. Mix the first mixture, 3-fluorophenol, 4-hydroxyphenylboric acid, formaldehyde (added as a 37% mass fraction formaldehyde aqueous solution), melamine, alkali (added as a 1 mol / L sodium hydroxide solution) and water (the mass ratio of water to 3-fluorophenol is 1:10) (stirring at 100 rpm for 30 min) and then hydrothermally react (react at 160°C for 4 h).
[0082] The preparation process of the antibacterial ceramic in the present application comprises the following steps:
[0083] Mixing kaolin, bauxite, feldspar, talc, quartz, dispersant, antibacterial agent, resin and water to prepare slurry, and shaping the slurry to prepare a green body;
[0084] The green body is fired and then cooled after firing;
[0085] Firing consists of the first heating, the first heat preservation, the second heating and the second heat preservation.
[0086] The first heating rate was 10°C / min.
[0087] The first insulation temperature is 500°C.
[0088] The first insulation time is 2h.
[0089] The second heating rate was 10°C / min.
[0090] The second insulation temperature is 1250°C.
[0091] The second insulation time is 12h.
[0092] Example 2
[0093] This embodiment is an antibacterial ceramic, which is composed of the following raw materials in parts by weight:
[0094] 100 parts of kaolin, 50 parts of bauxite, 100 parts of feldspar, 5 parts of talc, 50 parts of quartz, 10 parts of dispersant, 10 parts of resin, 0.2 parts of antibacterial agent and 100 parts of water.
[0095] The dispersant is composed of polyethylene glycol and sodium polyacrylate in a mass ratio of 1:1.
[0096] Feldspar is composed of albite and potassium feldspar, and the mass ratio of albite to potassium feldspar is 1:0.5.
[0097] The antibacterial agent is a compound of zinc oxide and silver ion antibacterial agent, and the mass ratio of zinc oxide to silver ion antibacterial agent is 1:2.
[0098] The resin includes the following raw materials in parts by weight:
[0099] 100 parts of 3-fluorophenol, 450 parts of 4-hydroxyphenylboric acid, 160 parts of formaldehyde, 100 parts of melamine, 100 parts of boric acid, 400 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0100] The preparation method of the resin in this example is carried out with reference to Example 1.
[0101] The preparation process of the antibacterial ceramic in this embodiment is carried out with reference to Example 1.
[0102] Example 3
[0103] This embodiment is an antibacterial ceramic, which is composed of the following raw materials in parts by weight:
[0104] 100 parts of kaolin, 100 parts of bauxite, 80 parts of feldspar, 10 parts of talc, 100 parts of quartz, 10 parts of dispersant, 20 parts of resin, 0.1 parts of antibacterial agent and 100 parts of water.
[0105] The dispersant is composed of polyethylene glycol and sodium polyacrylate in a mass ratio of 1:1.
[0106] Feldspar is composed of albite and potassium feldspar, and the mass ratio of albite to potassium feldspar is 1:2.
[0107] The antibacterial agent is a compound of zinc oxide and silver ion antibacterial agent, and the mass ratio of zinc oxide to silver ion antibacterial agent is 1:2.
[0108] The resin includes the following raw materials in parts by weight:
[0109] 100 parts of 3-fluorophenol, 400 parts of 4-hydroxyphenylboric acid, 200 parts of formaldehyde, 200 parts of melamine, 50 parts of boric acid, 300 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0110] The preparation method of the resin in this example is carried out with reference to Example 1.
[0111] The preparation process of the antibacterial ceramic in this embodiment is carried out with reference to Example 1.
[0112] Example 4
[0113] This embodiment is an antibacterial ceramic, which is composed of the following raw materials in parts by weight:
[0114] 100 parts of kaolin, 50 parts of bauxite, 50 parts of feldspar, 5 parts of talc, 50 parts of quartz, 10 parts of dispersant, 0.1 parts of antibacterial agent, 10 parts of resin and 100 parts of water.
[0115] The dispersant is composed of polyethylene glycol and sodium polyacrylate in a mass ratio of 1:1.
[0116] Feldspar is composed of albite and potassium feldspar, and the mass ratio of albite to potassium feldspar is 1:1.
[0117] The antibacterial agent is a compound of zinc oxide and silver ion antibacterial agent, and the mass ratio of zinc oxide to silver ion antibacterial agent is 1:2.
[0118] The resin includes the following raw materials in parts by weight:
[0119] 100 parts of 3-fluorophenol, 400 parts of 4-hydroxyphenylboric acid, 100 parts of formaldehyde, 100 parts of melamine, 50 parts of boric acid, 300 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0120] The preparation method of the resin in this example is carried out with reference to Example 1.
[0121] The preparation process of the antibacterial ceramic in this embodiment is carried out with reference to Example 1.
[0122] Example 5
[0123] This embodiment is an antibacterial ceramic, and the only difference from the embodiment 4 is that the preparation process of the antibacterial ceramic in this embodiment is different from that in the embodiment 4, as follows:
[0124] Mixing kaolin, bauxite, feldspar, talc, quartz, dispersant, antibacterial agent, resin and water to prepare slurry, and shaping the slurry to prepare a green body;
[0125] The green body is fired and then cooled after firing;
[0126] Firing consists of heating up and keeping warm.
[0127] The heating rate was 10°C / min.
[0128] The insulation temperature is 1250°C.
[0129] The insulation time is 14h.
[0130] Comparative Example 1
[0131] This comparative example is an antibacterial ceramic, which is composed of the following raw materials in parts by weight:
[0132] 100 parts of kaolin, 50 parts of bauxite, 50 parts of feldspar, 5 parts of talc, 50 parts of quartz, 10 parts of dispersant, 0.1 parts of antibacterial agent and 100 parts of water.
[0133] The dispersant and antibacterial agent are the same as those in Example 5.
[0134] The preparation process of the antibacterial ceramic in this comparative example comprises the following steps:
[0135] Mixing kaolin, bauxite, feldspar, talc, quartz, a dispersant, an antibacterial agent and water to prepare a slurry, and shaping the slurry to prepare a green body;
[0136] The green body is fired and then cooled after firing;
[0137] Firing consists of heating up and keeping warm.
[0138] The heating rate was 10°C / min.
[0139] The insulation temperature is 1250°C.
[0140] The insulation time is 14h.
[0141] Comparative Example 2
[0142] This comparative example is an antibacterial ceramic, which differs from Example 5 in that:
[0143] The resin includes the following raw materials in parts by weight:
[0144] 100 parts of 3-fluorophenol, 400 parts of 4-hydroxyphenylboric acid, 100 parts of formaldehyde, 50 parts of boric acid, 300 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0145] The preparation method of the resin in this comparative example consists of the following steps:
[0146] S1, mixing boric acid and phenyltriethoxysilane for reaction (reacting at 60° C. for 12 hours) to obtain a first mixture;
[0147] S2. Mix the first mixture, 3-fluorophenol, 4-hydroxyphenylboric acid, formaldehyde (added as a 37% mass fraction formaldehyde aqueous solution), alkali (added as a 1 mol / L sodium hydroxide solution) and water (the mass ratio of water to 3-fluorophenol is 1:10) (stirring at 100 rpm for 30 min) and then hydrothermally react (react at 160°C for 4 h).
[0148] The preparation process of the antibacterial ceramic in this comparative example is carried out with reference to Example 5.
[0149] Comparative Example 3
[0150] This comparative example is an antibacterial ceramic, which differs from Example 5 in that:
[0151] The resin includes the following raw materials in parts by weight:
[0152] 500 parts of 4-hydroxyphenylboric acid, 100 parts of formaldehyde, 100 parts of melamine, 50 parts of boric acid, 300 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0153] The preparation method of the resin in this comparative example consists of the following steps:
[0154] S1, mixing boric acid and phenyltriethoxysilane for reaction (reacting at 60° C. for 12 hours) to obtain a first mixture;
[0155] S2. Mix the first mixture, 4-hydroxyphenylboric acid, formaldehyde (added as a 37% mass fraction formaldehyde aqueous solution), melamine, alkali (added as a 1 mol / L sodium hydroxide solution) and water (the mass ratio of water to 3-fluorophenol is 1:10) (stirring at 100 rpm for 30 min) and then hydrothermally react (react at 160°C for 4 h).
[0156] The preparation process of the antibacterial ceramic in this comparative example is carried out with reference to Example 5.
[0157] Comparative Example 4
[0158] This comparative example is an antibacterial ceramic, which differs from Example 5 in that:
[0159] The resin includes the following raw materials in parts by weight:
[0160] 500 parts of 3-fluorophenol, 100 parts of formaldehyde, 100 parts of melamine, 50 parts of boric acid, 300 parts of phenyltriethoxysilane and 4 parts of alkali (sodium hydroxide).
[0161] The preparation method of the resin in this comparative example consists of the following steps:
[0162] S1, mixing boric acid and phenyltriethoxysilane for reaction (reacting at 60° C. for 12 hours) to obtain a first mixture;
[0163] S2. Mix the first mixture, 3-fluorophenol, formaldehyde (added as a 37% mass fraction formaldehyde aqueous solution), melamine, alkali (added as a 1 mol / L sodium hydroxide solution) and water (the mass ratio of water to 3-fluorophenol is 1:10) (stirring at 100 rpm for 30 min) and then hydrothermally react (react at 160°C for 4 h).
[0164] The preparation process of the antibacterial ceramic in this comparative example is carried out with reference to Example 5.
[0165] Comparative Example 5
[0166] This comparative example is an antibacterial ceramic, which differs from Example 5 in that:
[0167] The resin includes the following raw materials in parts by weight:
[0168] 100 parts of 3-fluorophenol, 400 parts of 4-hydroxyphenylboric acid, 100 parts of formaldehyde, 100 parts of melamine and 4 parts of alkali (sodium hydroxide).
[0169] The preparation method of the resin in this comparative example consists of the following steps:
[0170] 3-Fluorophenol, 4-hydroxyphenylboronic acid, formaldehyde (added as a 37% mass fraction formaldehyde aqueous solution), melamine, alkali (added as a 1 mol / L sodium hydroxide solution) and water (the mass ratio of water to 3-fluorophenol is 1:10) are mixed (stirred at 100 rpm for 30 min) and then hydrothermally reacted (reacted at 160°C for 4 h).
[0171] The preparation process of the antibacterial ceramic in this comparative example is carried out with reference to Example 5.
[0172] According to JC / T 897 “Antibacterial Properties of Antibacterial Ceramic Products”, the antibacterial rates of the samples made of the antibacterial ceramic materials of each embodiment and comparative example were tested. The test results are shown in Table 1.
[0173] Table 1
[0174] - Compressive strength(MPa) Antibacterial rate (%) Example 1 186 99.31 Example 2 172 99.78 Example 3 178 99.23 Example 4 169 99.18 Example 5 153 99.15 Comparative Example 1 79 95.02 Comparative Example 2 104 99.10 Comparative Example 3 98 99.25 Comparative Example 4 87 96.36 Comparative Example 5 93 98.32
[0175] The difference between Example 5 and Example 4 is that Example 5 is sintered once, while Example 4 is sintered twice, that is, the process of promoting phase generation in Example 5 is shorter. Therefore, the compressive strength of Example 5 is poorer than that of Example 4.
[0176] The difference between Example 5 and Comparative Example 1 is that no resin material is added in Comparative Example 1, while the resin of the present application plays a role in the introduction of both the reinforcing phase and the antibacterial factor, and therefore, the compressive strength and antibacterial performance are significantly reduced.
[0177] The difference between Example 5 and Comparative Example 2 is that no melamine is added in Comparative Example 2, and therefore less reinforcing phase (silicon nitride or boron nitride, etc.) is formed, resulting in lower compressive strength.
[0178] The difference between Example 5 and Comparative Example 3 is that in Comparative Example 3, 3-fluorophenol is not added, and there is no process of promoting phase formation, which results in lower compressive strength.
[0179] The difference between Example 5 and Comparative Example 4 is that 4-hydroxyphenylboric acid is not added in Comparative Example 4, and the amount of boron introduced is relatively reduced, resulting in less introduction of reinforcing phase and antibacterial factors, thereby resulting in a decrease in compressive strength and antibacterial rate.
[0180] The difference between Example 5 and Comparative Example 5 is that boric acid and phenyltriethoxysilane are not added in Comparative Example 5, resulting in a reduction in the silicon reinforcement phase introduced in situ, thereby resulting in a lower compressive strength.
[0181] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An antibacterial ceramic, characterized in that: The preparation comprises the following raw materials in parts by weight: 100 parts of kaolin, 50 to 100 parts of bauxite, 50 to 100 parts of feldspar, 5 to 10 parts of talc, 50 to 100 parts of quartz, 5 to 10 parts of dispersant, 0.1 to 0.2 parts of antibacterial agent and 10 to 30 parts of resin; The resin comprises the following raw materials in parts by weight: 100 parts of 3-fluorophenol, 400 to 500 parts of 4-hydroxyphenylboric acid, 100 to 200 parts of formaldehyde, 100 to 200 parts of melamine, 50 to 100 parts of boric acid, 300 to 400 parts of phenyltriethoxysilane and 1 to 10 parts of alkali; The method for preparing the resin comprises the following steps: S1, mixing boric acid and phenyltriethoxysilane to react to obtain a first mixture; S2, mixing the first mixture, 3-fluorophenol, 4-hydroxyphenylboric acid, formaldehyde, melamine, alkali and water and then hydroheating; The reaction temperature in step S1 is 60°C to 80°C; The reaction time of step S1 is 10h~20h; The hydrothermal temperature in step S2 is 150°C to 170°C; The hydrothermal time in step S2 is 3h~5h.
2. The antibacterial ceramic according to claim 1, characterized in that: The dispersant includes at least one of polyethylene glycol and sodium polyacrylate.
3. The antibacterial ceramic according to claim 1, characterized in that: The antibacterial agent is a compound of zinc oxide and silver ion antibacterial agent; The mass ratio of the zinc oxide to the silver ion antibacterial agent is 1:1.9-2.
1.
4. The antibacterial ceramic according to claim 1, characterized in that: The raw materials for preparing the antibacterial ceramic also include water; The mass ratio of kaolin to water is 1:0.5-1.
5.
5. The antibacterial ceramic according to claim 1, characterized in that: The base includes at least one of sodium hydroxide and ammonia monohydrate.
6. The antibacterial ceramic according to claim 1, characterized in that: The flexural strength of the antibacterial ceramic is 150MPa~200Mpa; And / or, the antibacterial rate of the antibacterial ceramic is 95% to 99.9%.
7. A process for preparing the antibacterial ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing kaolin, bauxite, feldspar, talc, quartz, dispersant, antibacterial agent, resin and water to prepare slurry, and shaping the slurry to prepare a green body; Firing the green body; The firing temperature is 400°C to 1300°C.
8. The preparation process according to claim 7, characterized in that: The firing includes a first heat preservation and a second heat preservation; The temperature of the first insulation is 400°C to 600°C; The first insulation time is 2h~4h; The temperature of the second insulation is 1200° C. to 1300° C.; The second insulation time is 10h~14h.
Citation Information
Patent Citations
Wear-resistant mildew-proof ceramic material, wear-resistant mould-proof ceramic tile and preparation method of wear-resistant mould-proof ceramic tile
CN111548118A
Antibacterial self-cleaning ceramic glaze and preparation method thereof
CN113149436A